Lilly Tes-Tape Urine Sugar Analysis Paper (1970)
Three close-up views of Tes-Tape Urine Sugar Analysis Paper manufactured by Eli Lilly and Company.
Keywords: Medical care; Diabetes; Urine--Analysis; Diabetes--Treatment; Medical supplies; Medical supplies industry